2002
DOI: 10.1016/s0736-0266(01)00081-x
|View full text |Cite
|
Sign up to set email alerts
|

The knee adduction moment during gait in subjects with knee osteoarthritis is more closely correlated with static alignment than radiographic disease severity, toe out angle and pain

Abstract: This study tested whether the peak external knee adduction moments during walking in subjects with knee osteoarthritis (OA) were correlated with the mechanical axis of the leg, radiographic measures of OA severity, toe out angle or clinical assessments of pain, stiffness or function. Gait analysis was performed on 62 subjects with knee OA and 49 asymptomatic control subjects (normal subjects). The subjects with OA walked with a greater than normal peak adduction moment during early stance 0, = 0.027). In the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
374
12
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(429 citation statements)
references
References 15 publications
27
374
12
16
Order By: Relevance
“…The magnitude of knee adduction moment is influenced by the magnitude of the ground reaction force, the moment arm, and the mass and acceleration of lower limb segments (Fig. 4) [12,22]. Peak knee adduction moment represents the maximum load differential between the medial and lateral compartment during one gait cycle.…”
Section: Gait Analysismentioning
confidence: 99%
“…The magnitude of knee adduction moment is influenced by the magnitude of the ground reaction force, the moment arm, and the mass and acceleration of lower limb segments (Fig. 4) [12,22]. Peak knee adduction moment represents the maximum load differential between the medial and lateral compartment during one gait cycle.…”
Section: Gait Analysismentioning
confidence: 99%
“…Numerous variables have been studied regarding their usefulness for predicting the progression of knee OA (Table 4) [13,15,23,35,47]; however, amid conflicting reports, few predictive variables have strong supporting evidence [51]. We found that the radiographic medial knee JS and the peak knee adduction angle were the best predictors of knee pain in our study; and that these variables accounted for approximately three-quarters of the model variance (r 2 = 0.73).…”
Section: Discussionmentioning
confidence: 52%
“…Gait alterations are often seen in people with knee OA during walking, which have been suggested to be an attempt to reduce pain and joint load (21,41). People with knee OA typically walk more slowly and with a reduced knee ROM during early stance, as well as a reduced total knee ROM, compared to asymptomatic control subjects (20,21).…”
Section: Discussionmentioning
confidence: 99%